Gel Immersion Endoscopic Mucosal Resection (EMR) for Superficial Nonampullary Duodenal Epithelial Tumors May Reduce Procedure Time Compared with Underwater EMR (with Video). (15th June 2022) - Yamashina, Takeshi; Shimatani, Masaaki; Takahashi, Yu; Takeo, Masahiro; Saito, Natsuko; Matsumoto, Hironao; Kasai, Takeshi; Kano, Masataka; Sumimoto, Kimi; Mitsuyama, Toshiyuki; Marusawa, Hiroyuki; Nishio, Akiyoshi; et al.
Abstract : Background/Aims . Underwater endoscopic mucosal resection (UEMR) has recently attracted attention as a safe and effective method for superficial nonampullary duodenal epithelial tumors (SNADETs). However, water is a fluid and it does not remain in all areas, and because it mixes easily with other substances, it sometimes becomes cloudy and reduces visibility. A new endoscopic gel product that does not mix with fluids and tends to remain in the injected area has recently been applied to EMR and is known as gel immersion EMR (GIEMR) or under-gel EMR. Here, we evaluated the endoscopic outcomes of UEMR and GIEMR. Materials and Methods . This was a retrospective cohort study conducted in two municipal hospitals. We identified 24 patients with SNADETs of 3–18 mm in diameter who underwent UEMR or GIEMR. One lesion was excluded from the analysis because it was found to be in the stomach after surgery. The primary outcome was procedure time. Results . GIEMR significantly reduced the procedure time compared with UEMR (5 min vs. 10 min, P = 0.016 ). There was no significant difference between the UEMR and GIEMR groups for en bloc resection rate (93% vs. 100%, P = 1.0 ) and R0 resection rate (57% vs. 80%, P = 0.39 ). No serious complications were observed in either group. Conclusions . GIEMR of SNADET has the potential to reduce procedure time compared with UEMR and may be particularly effective in areas where immersion in water is difficult.